2018
DOI: 10.3892/ijo.2018.4520
|View full text |Cite
|
Sign up to set email alerts
|

Nogo‑B receptor in relevant carcinoma: Current achievements, challenges and aims (Review)

Abstract: The novel neurite outgrowth inhibitor B (Nogo‑B) receptor (NgBR) is specific for Nogo‑B, which is highly expressed in various human organs and cells, including the lung, liver, kidney, smooth muscle cells, blood vessel endothelial cells and inflammatory cells. Previous studies have indicated that NgBR directly interacts with Nogo‑B and is able to independently influence lipid and cholesterol homeostasis, angiogenesis, N‑glycosylation, the epithelial-mesenchymal transition, the chemotaxis of endothelial cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…It is primarily located in the endoplasmic reticulum. NgBR plays a crucial in lipid and cholesterol homeostasis through direct interaction with Nogo-B, and in uences N-linked protein glycosylation by regulating the cis-PTase activity (Harrison et al, 2011;Li et al, 2018). Functional experiments showed that the loss of Drosophila NUS1 orthologous gene tango14 leads to motor de cits, reduces the number of apoptotic dopaminergic neurons and dopamine contents in Drosophila, and results in cholesterol accumulation in the Malpighian tubules and brain, as well as the formation of neurodegenerative brain vacuoles in an age dependent manner (Guo et Park et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is primarily located in the endoplasmic reticulum. NgBR plays a crucial in lipid and cholesterol homeostasis through direct interaction with Nogo-B, and in uences N-linked protein glycosylation by regulating the cis-PTase activity (Harrison et al, 2011;Li et al, 2018). Functional experiments showed that the loss of Drosophila NUS1 orthologous gene tango14 leads to motor de cits, reduces the number of apoptotic dopaminergic neurons and dopamine contents in Drosophila, and results in cholesterol accumulation in the Malpighian tubules and brain, as well as the formation of neurodegenerative brain vacuoles in an age dependent manner (Guo et Park et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It also regulates the glycosylation and stability of nascent NPC2, thereby promoting trafficking of LDL-derived cholesterol. Meanwhile, NUS1 has been widely documented to regulate cell growth, adhesion, and differentiation [37]. In addition, there is growing evidence that NUS1 is upregulated in several cancer types, such as breast cancer [38], liver cancer [39,40], and lung cancer [41].…”
Section: Discussionmentioning
confidence: 99%
“…AMPK, a serine/threonine kinase, is characterized by sensitivity to changes in the ratio of AMP/ATP; AMPK acts as a cellular energy sensor, regulating various cell progression processes such as CRC cell survival, proliferation, differentiation, migration and metabolism [122,123].…”
Section: The Function and Mechanism Of Ampk A Key Energy Metabolism mentioning
confidence: 99%